Metabolomic Biomarkers of Multiple Sclerosis: A Systematic Review - Porter, Lachlan; Shoushtarizadeh, Alireza; Jelinek, George A.; Brown, Chelsea R.; Lim, Chai K.; de Livera, Alysha M.; Jacobs, Kelly R.; Weiland, Tracey J. (Frontiers in Molecular Biosciences, 2020)
BACKGROUND: Magnetic Resonance Imaging (MRI), Cerebrospinal Fluid (CSF) analysis and the McDonald’s clinical criteria are currently utilized tools in diagnosing Multiple Sclerosis. However, a more conclusive, consistent and efficient way of diagnosing Multiple Sclerosis (MS) is yet to be discovered . A potential biomarker, discovered using advances in high throughput sequencing such as Nuclear Magnetic Resonance (NMR) Spectroscopy and other ‘Omics’ based techniques, may make diagnosis and prognosis more reliable resulting in a more personalized and targeted treatment regime and improved outcomes. The aim of this review was to systematically search the literature for potential biomarkers from any bodily fluid that could consistently and accurately diagnose MS and/or indicate disease progression. METHODS: A systematic literature review of EMBASE, PubMed (MEDLINE), The Cochrane Library and CINAHL databases produced over a thousand potential studies. Inclusion criteria stated studies with potential biomarker outcomes for people with MS were to be included in the review. Studies were limited to those with human participants who had a clinically defined diagnosis of MS and published in English; with no limit placed on date of publication nor the type of bodily fluid sampled. RESULTS: A total of 1805 studies were recorded from the literature search. 1760 studies were removed based on their abstract, with a further 18 removed after considering the full text. 27 studies were considered relevant and had their data retrieved and analysed. Due to the heterogeneity of focus and results from the refined studies, a narrative synthesis was favored. CONCLUSION: Several promising candidate biomarkers suitable for clinical application in MS have been studied. It is recommended follow up studies with larger sample sizes be completed on several potential biomarkers.